Spin effects from Four Bosons EM (JOURNAL OF ADVANCES IN PHYSICS, 2023)
Electromagnetism is the theory of electric charge and spin. Our study is on a spin-valued four bosons electromag- netism. An EM under the charge exchange {+, 0, −} intermediated by four bosons AμI ≡ {Aμ, Uμ, V ± μ } where Aμ means the usual photon, Uμ a massive photon, V ± μ charged photons. EM should express electric charge and spin together. Understand from first principles on the spin role in the electric and magnetic properties of particles. Theoretically, the spin is a space-time physical entity derived from Lorentz group. Phenomenologically, it appears as a vectorial entity inserted in the magnetic moment and electric dipole. A theoretical closure between them is expected. A spin-valued four bosons EM is constituted by introducing Lorentz group Lie Algebra valued fields. Consider the quadruplet fields as A I μ = A I μ,κλ(Σκλ)αβ where (Σκλ)αβ is the Lorentz generator. It provides spin as an intrinsec entity compatible with relativity and group theory. Similarly to the non-abelian gauge theory, where Aμa = Aμata, one incorporates the spin valued field through a Lie algebra. From first principles. Electric charge and spin are unified under a constructivist Lagrangian. Spin effects arestudied through equations of motion and Bianchi identities. Enlarging the EM for interactions beyond electric charge. Four types are derived. Usual electric charge interaction, neutral interaction, electric charge and spin, neutral and spin. A formalism is expressed. The spin valued performance is related through a Lagrangian. Spin interactions are derived. The magnetic moment and electric dipole are expressed by vectors S~ and ~s respectivity. They are able to couple spin with granular and collective fields strengths. Developing interacting terms constitutive as B~ · S~, E~ · ~s, ~e · S~ and so on. Faraday interaction between magnetic field and photon is reproduced from first principles.